(untitled) (Bangladesh Journal of Medical Science, 2019)
Background: Many putative genes were predicted as risk factors of schizophrenia. One of these genes is DTNBP1 gene. One of single nucleotide polymorphism (SNPs) of DTNBP1 gene is P1635 (rs3213207). Objective: This study aimed to find out the association between DTNBP1 gene, P1635 (rs3213207), and risk of schizophrenia. Methods: DNA was isolated from blood of 25 schizophrenia patients and 25 healthy controls. DNA was applied to restriction fragment length polymorphism polymerase chain reaction (RFLP PCR). PCR products were digested by BSr1 enzyme. Results: The results show that there are 24 AA genotype (wild type) from 25 Javanese schizophrenia patients and 1 GG homozygote, while all 25 of controls are AA genotype (wild type). The p value of Fisher’s exact test is 0,500. Conclusion: There is no significant differences of genotype distribution of SNP P 1635(rs3213207) between schizophrenia patients and healthy controls in Javanese population Bangladesh Journal of Medical Science Vol.18(4) 2019 p.703-705